2022
DOI: 10.1371/journal.pone.0270091
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate dental students’ perspective of online learning and their physical and mental health during COVID-19 pandemic

Abstract: Background and objective COVID-19 pandemic continuously spread exacerbating global concerns. It had impacted all life aspects such as social, cultural, economic and education. This study assess the impact of COVID-19 pandemic on undergraduate dental students at Faculty of Dentistry, University of Malaya. The objective of this study is to evaluate the impact of the pandemic on physical and mental health of undergraduate dental students. Methods This is a cross-sectional study. An online questionnaire was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
1
17
0
6
Order By: Relevance
“…The negative impacts of the COVID-19 pandemic on the finances and mental health of the students cannot be underestimated, with many of the students commenting on how scared they felt not only in the clinical environment but also with the situation in general, which is in keeping with other studies [ 14 , 18 , 34 ]. However, the majority of them felt that the extension was necessary to prepare them to become a safe beginner and to prepare them for the next stage of their career.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The negative impacts of the COVID-19 pandemic on the finances and mental health of the students cannot be underestimated, with many of the students commenting on how scared they felt not only in the clinical environment but also with the situation in general, which is in keeping with other studies [ 14 , 18 , 34 ]. However, the majority of them felt that the extension was necessary to prepare them to become a safe beginner and to prepare them for the next stage of their career.…”
Section: Discussionsupporting
confidence: 81%
“…The conclusion was that all students in all of the years of the BDS programme in Dundee and Glasgow would be required to undertake a 1-year extension to reach the status of ‘safe beginner’ for registration with the General Dental Council [ 17 ]. The decision undoubtedly affected the students at many different levels, but there are reports on the adverse impact of COVID-19 on the dental students’ stress levels [ 14 , 18 ], and no accounts could be found on the impact on their clinical experience in comparison to that of the pre-COVID-19 levels or of other extensions to the dental course.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is not consistent with Etajuri et al in which only 49.7% of the dentistry students were satisfied with the clinical knowledge delivered through online classes. This fact may be related to the limited manual training and lack of interaction with the patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In online education, group learning occurs through social interaction (18). A previous study concluded that while dental students can adapt to online learning, they are concerned about their physical and mental health (19). Another study reported that distance education encouraged students to learn on their own and it improved their ability to use online resources (20), whereas other studies reported that face-to-face education is more effective than online education (15,21).…”
Section: Discussionmentioning
confidence: 99%